Computers in Cardiology, 2004
DOI: 10.1109/cic.2004.1442885
|View full text |Cite
|
Sign up to set email alerts
|

Automated prediction of spontaneous termination of atrial fibrillation from electrocardiograms

Abstract: Abs trsc t An algorithm for differentiating ECGs with atriul fibrillation (A F) that will spontaneously terminate within 60 seconds from signals, where it won't, has been developed using the AF Termiliation Challenge Database from PhysioNet. The algorithm was based on the calculation of the major AF frequency by canceling out the QRS complexes and T waves from the original ECGs and then applying short time Fourier transform techniques to the remaining signals. The mujor AF frequency and the mean RR interval we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…These results demonstrate that AF of N type behaves more randomly and oscillates more dramatically. This matches the conclusion obtained by Hayn et al [21], who studied the relation between dominant peak frequency (DAF) and degree of organization of AF. Meanwhile, the correlation coefficient between IS and mIF using linear regression analysis is 0.56 (p 5 0.01).…”
Section: Resultssupporting
confidence: 87%
“…These results demonstrate that AF of N type behaves more randomly and oscillates more dramatically. This matches the conclusion obtained by Hayn et al [21], who studied the relation between dominant peak frequency (DAF) and degree of organization of AF. Meanwhile, the correlation coefficient between IS and mIF using linear regression analysis is 0.56 (p 5 0.01).…”
Section: Resultssupporting
confidence: 87%
“…Additionally, t test revealed that the SampEn of f p1 has the highest predictive power among all the studied spectral parameters. In previous studies of the AF termination [9,16,29], f p1 has been also revealed as a good predictor of AF termination. The main difference between our work and those studies is that we consider the mathematical regularity of spectral parameters in opposition to direct mean values.…”
Section: Discussionmentioning
confidence: 92%
“…Several groups based their study on the atrial activity (AA) overall peak frequency plus additional spectral characteristics as the main peak power [29] or time-frequency pattern [26]. Other groups tried to predict the evolution of PAF episodes by means of linear classifiers based on the main peak frequency and the mean RR interval [9,16]. In [28], the fibrillation frequency, fibrillation amplitude and exponential decay are extracted from a frequency-shifted and amplitude-scaled version of a log-spectral profile.…”
Section: Introductionmentioning
confidence: 99%
“…The features analyzed were selected by the article who obtained the best results in the completion, and therefore the way they processed the ECG and the characteristics they used should, in theory, be representative of the recordings. In total 55 different characteristics were used, from the following articles : Cantini et al (2004), Lemay et al (2004), Hayn et al (2004), Raine and Langley (2004), Mora and Castells (2004), Scherr et al (2007), Petrutiu et al (2006), and Chiarugi et al (2007).…”
Section: Feature Extractionsmentioning
confidence: 99%